REKRUTMEN POLITIK PARTAI HATI NURANI RAKYAT (HANURA) PADA PEMILIHAN UMUM LEGISLATIF DI KOTA PEKANBARU TAHUN 2014 - Sugeng "; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Political parties have a position and a very important role in the democratic system. Political parties play a role as a strategic link between the processes of government to citizens. Every political party has a different recruitment pattern, where the pattern of recruitment of party members adapted to the political system that was followed. In recruiting candidates for legislative in 2014, DPC Hanura Pekanbaru city does not provide equal opportunities to all citizens melain to Hanura own cadres and cadres of the Party coalition to compete in the process of selecting candidates for legislative. The theory used is the mechanism for recruitment of Czudnowski (in Fadillah Son, 2003) which has two properties, namely: open and closed. By using three indicators, namely: the provision of recruitment, criteria and control candidates for legislative. The type of approach used is qualitative by using the case study method to describe and analyze patterns of recruitment DPC HANURA Party. Subject is Hanura give freedom or the same opportunity to the party cadres coalition to Hanura to become candidates for legislative. Keywords: Political parties, Political Recruitment, Candidates for Legislative